Role of Abdominal Drain Post Open Appendectomy for Perforated Appendicitis Among acute appendicitis patients admitted to surgical ward in Al-Thawra Modern General Hospital and Al-Kuwait University Hospital from march 2022 to march 2023 - Issa, Mohammed Ali; Obadiel, Yasser Abdurabu; Al-Tanobi, Abdulbaset Ahmed Hasen (Journal of medical and pharmaceutical sciences, 2024)
Background : Acute appendicitis is the most common cause of surgical acute abdomen. Perforation of appendicitis is associated with increase risk of postoperative complications and mortality. Routine peritoneal drainage after appendectomy for perforated appendicitis remains a topic of debate. Objectives: To evaluate the benefit of abdominal drainage post open appendectomy for perforated appendicitis and to study the impact of abdominal drainage on post-operative complications and on length of hospital stay. Methods: A cross-sectional, observational, prospective study was conducted among 85 Patients with perforated appendicitis who underwent open appendectomy Al-Thawra Modern General Hospital and Al-Kuwait University Hospital in Sana’a city from March 2022 to March 2023..Data was analyzed using the statistic package SPSS 23. Results: 85 patients were classified into two groups based on intra-operative insertion of abdominal drainage. There were 50 patients in the drain group compared to 35 patients in the no-drain group. In both groups, majority of patients were male. Most of patients in both groups were in the age group (11-25 years). The main complain of patients was pain, which started around umbilicus, then shifted to right iliac fossa. All patients in both group had tenderness in right iliac fossa. Fever and rebound tenderness were prominent signs in both groups. Leukocytosis was present in 68 % of patients in the drain group compared to 80% in the no drain group. Most of patients in both groups had longer duration of symptoms for three days and more. The tip of appendix was the most common site of perforation in both groups. Surgical site infection occurred in 5 patients (10%) in the drain group compared to 2 patients (5.7%) in the no-drain group. Intra-abdominal abscess occurred in one patient in each the drain group and the no-drain group. Postoperative ileus occurred in one patient in the drain group compared to no patients in the no-drain group.